2014
DOI: 10.1097/mnm.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mediastinal lymph node metastasis in non-small-cell lung cancer by PET/CT

Abstract: The mediastinal lymph node metastasis ratio was correlated with SUV(max), size, and differentiation in primary lung lesions. SUV(max) was the only independent predictor of lymph node metastasis in NSCLC. Video Abstract: http://links.lww.com/NMC/A22.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Because the AUCs for SUV n/t and SUV max were not particularly informative, we hypothesized that tumor diameter may also influence the diagnostic accuracy because bigger or higher-stage tumors would have a greater possibility of LN metastasis. [2224] We therefore assessed the diagnostic efficiency of SUV index , defined as SUV n/t multiplied by maximal tumor diameter on PET/CT. According to the results, SUV index (AUC 0.71, 95% CI 0.64–0.78) provided a better predictive index of mediastinal LN malignancy in lung cancer patients than SUV max or SUV n/t .…”
Section: Discussionmentioning
confidence: 99%
“…Because the AUCs for SUV n/t and SUV max were not particularly informative, we hypothesized that tumor diameter may also influence the diagnostic accuracy because bigger or higher-stage tumors would have a greater possibility of LN metastasis. [2224] We therefore assessed the diagnostic efficiency of SUV index , defined as SUV n/t multiplied by maximal tumor diameter on PET/CT. According to the results, SUV index (AUC 0.71, 95% CI 0.64–0.78) provided a better predictive index of mediastinal LN malignancy in lung cancer patients than SUV max or SUV n/t .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been undertaken to investigate the relationship between standard uptake value (SUV) of primary lung cancer lesions and node involvement, and the results showed that SUV max of the primary tumor might be an independent predictor of regional lymph node metastasis in patients with NSCLC. CT is widely used as the standard of care procedure used routinely for assessing NSCLC, and the vast majority of lung cancer patients undergo only chest CT as their diagnostic procedure.…”
Section: Introductionmentioning
confidence: 99%